27.04.2015 Views

Computability and Logic

Computability and Logic

Computability and Logic

SHOW MORE
SHOW LESS

You also want an ePaper? Increase the reach of your titles

YUMPU automatically turns print PDFs into web optimized ePapers that Google loves.

19.1. DISJUNCTIVE AND PRENEX NORMAL FORMS 245<br />

Proof: Given any formula, first replace it by a negation-normal equivalent. Then,<br />

using the distributive laws, that is, the equivalence of (B &(C ∨ D)) to ((B & C) ∨<br />

(B & D)) <strong>and</strong> of ((B ∨ C)&D) to((B ∨ D)&(C ∨ D)), ‘push conjunction inside’<br />

<strong>and</strong> ‘pull disjunction outside’ until a disjunctive normal equivalent is obtained.<br />

(It would be a tedious but routine task to rewrite this ‘top down’ description of the<br />

process of finding a disjunctive normal equivalent as a ‘bottom up’ proof the existence<br />

of such an equivalent.)<br />

If in a formula that is in disjunctive normal form each disjunction contains each<br />

A i exactly once, plain or negated, then the compound is said to be in full disjunctive<br />

normal form. (A notion of full conjunctive normal form can be defined exactly analogously.)<br />

In connection with such forms it is often useful to introduce, in addition to<br />

the two-place connectives ∨ <strong>and</strong> & , <strong>and</strong> the one-place connective ∼, the zero-place<br />

connectives or constant truth ⊤ <strong>and</strong> constant falsehood ⊥, counting respectively as<br />

true in every interpretation <strong>and</strong> false in every interpretation. The disjunction of zero<br />

disjuncts may by convention be understood to be ⊥, <strong>and</strong> the conjunction of zero conjuncts<br />

to be ⊤ (rather as, in mathematics, the sum of zero summ<strong>and</strong>s is understood<br />

to be 0, <strong>and</strong> the product of zero factors to be 1).<br />

In seeking a full disjunctive normal equivalent of a given disjunctive normal formula,<br />

first note that conjunctions (<strong>and</strong> analogously, disjunctions) can be reordered<br />

<strong>and</strong> regrouped at will using the commutative <strong>and</strong> associative laws, that is, the equivalence<br />

of (B & C)to(C & B), <strong>and</strong> of (B & C & D), which officially is supposed to be<br />

an abbreviation of (B &(C & D)), with grouping to the right, to ((B & C)&D), with<br />

grouping to the left. Thus for instance (P &(Q & P)) is equivalent to (P &(P & Q))<br />

<strong>and</strong> to ((P & P)&Q). Using the idempotent law, that is, the equivalence of B & B<br />

to B, this last is equivalent to P & Q. This illustrates how repetitions of the same A i<br />

(or ∼A i ) within a conjunction can be eliminated. To eliminate the occurrence of the<br />

same A i twice, once plain <strong>and</strong> once negated, we can use the equivalence of B & ∼B to<br />

⊥ <strong>and</strong> of ⊥ & C to ⊥, <strong>and</strong> of ⊥∨D to D, so that, for instance, (B & ∼B & C) ∨ D is<br />

equivalent simply to D: contradictory disjuncts can be dropped. These reductions will<br />

convert a given formula to one that, like our earlier example (∼P & Q) ∨ (∼P & R),<br />

is a disjunction of conjunctions in which each basic formula occurs at most once,<br />

plain or negated, in each conjunct.<br />

To ensure that each occurs at least once in each conjunction, we use the equivalence<br />

of B to (B & C) ∨ (B & ∼C). Thus our example is equivalent to<br />

<strong>and</strong> to<br />

(∼P & Q & R) ∨ (∼P & Q & ∼R) ∨ (∼P & ∼R)<br />

(∼P & Q & R) ∨ (∼P & Q & ∼R) ∨ (∼P&Q & ∼R) ∨ (∼P & ∼Q & ∼R)<br />

<strong>and</strong>, eliminating repetition, to<br />

(∼P & Q & R) ∨ (∼P & Q & ∼R) ∨ (∼P & ∼Q & ∼R)<br />

which is in full disjunctive normal form. The foregoing informal description can be<br />

converted into a formal proof of the following result.

Hooray! Your file is uploaded and ready to be published.

Saved successfully!

Ooh no, something went wrong!